Sequence of maximal distance codes in graphs or other metric spaces - Charles Delorme (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2013)
Given a subset C in a metric space E, its successor is the subset s(C) of points at maximum distance from C in E. We study some properties of the sequence obtained by iterating this operation. Graphs with their usual distance provide already typical examples.